2014
DOI: 10.1371/journal.pone.0086170
|View full text |Cite
|
Sign up to set email alerts
|

Sticky Tunes: How Do People React to Involuntary Musical Imagery?

Abstract: The vast majority of people experience involuntary musical imagery (INMI) or ‘earworms’; perceptions of spontaneous, repetitive musical sound in the absence of an external source. The majority of INMI episodes are not bothersome, while some cause disruption ranging from distraction to anxiety and distress. To date, little is known about how the majority of people react to INMI, in particular whether evaluation of the experience impacts on chosen response behaviours or if attempts at controlling INMI are succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 27 publications
4
77
0
1
Order By: Relevance
“…We report on the development of IMIS, a new self-report scale, which ranging from pleasant and neutral (Beaman & Williams, 2010;Halpern & Bartlett, 2011) to annoying and disturbing (Hemming, 2009;Williamson et al, 2014 an implication in previous studies. Beaman and Willliams (2010) found that the chorus is the part of a song most often experienced as INMI, which usually contains a catchy "vocal hook" (Kachulis, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report on the development of IMIS, a new self-report scale, which ranging from pleasant and neutral (Beaman & Williams, 2010;Halpern & Bartlett, 2011) to annoying and disturbing (Hemming, 2009;Williamson et al, 2014 an implication in previous studies. Beaman and Willliams (2010) found that the chorus is the part of a song most often experienced as INMI, which usually contains a catchy "vocal hook" (Kachulis, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaire item writing was informed by an extensive review of the INMI literature and existing scales/questionnaires. In addition, we drew on thousands of reports from individuals contained within our pre-existing database of INMI reports (see Müllensiefen et al, 2014a;Williamson et al, 2012;Williamson et al, 2014). A 5-point frequency scale (ranging from Always to Never) was used for all 68 items, with an additional category of Not Applicable (N/A) in order to identify and exclude items that were not considered relevant by participants.…”
Section: Methodsmentioning
confidence: 99%
“…The duration of an INMI episode is reported to range from a few minutes to several hours (Beaman & Williams, 2010) and familiar music with lyrics is experienced as INMI more often than instrumental music (Liikkanen, 2012a). The valence attributed to INMI is mostly positive (Beaman & Williams, 2010;Floridou & Müllensiefen, 2015;Halpern & Bartlett, 2011;Hyman et al, 2013) although people can be significantly troubled by the experience and employ amelioration strategies such as listening to the INMI music or distracting themselves with other music or verbal activities (Williamson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Earworms are mostly perceived as neutral or even fun, although 30% of respondents in surveys labelled earworms as disturbing. 3 Very few patients will discuss this with their physician, and probably even fewer physicians will actively enquire about it. To distinguish between common physiology and possible pathology, the following clues are helpful.…”
mentioning
confidence: 99%
“…Treatment aims to improve successful coping, rather than eradicating earworms. Two successful strategies can be distinguished: engagement, for example, singing the song aloud; and distraction, for example, doing sports, listening to different music, 3 or even chewing gum. A variety of self-help options can be found on the internet.…”
mentioning
confidence: 99%